2014
DOI: 10.1016/j.ejmech.2014.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of azaisoerianin derivatives as potential antitumors agents

Abstract: A series of N-methyl-diarylamines 2 was designed and synthesized as a novel class of CA-4 and isoCA-4 analogues. Compounds 2b and 2m showed excellent antiproliferative activity with mean GI50 values at a nanomolar level in a diverse set of human cancer cells. These compounds also inhibited tubulin assembly at a micromolar range, arrested the cellular cycle in the G2/M phase and induced apoptosis at very low concentrations. Preliminary in vitro results revealed that 2b and 2m displayed substantial efficacy as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Seven compounds-4a, 4b, 4c, 4d, 4i, 4k,a nd 4l-were found to have strong growth inhibitory activity against HCT116 cells, with GI 50 values lower than 50 nm.A sw ep reviously observed with other isoCA-4 analogues, [17,21,34,35] compounds 4b,4c ,a nd 4d,w hich respectively bear the greatest resemblancet oisoCA-4, isoFCA-4, and iso-NH 2 CA-4, possessed the highest potency,i nhibiting the growth of HCT116 cells with GI 50 values ranging from 10 to 18 nm. These GI 50 values are similart ot hose obtained with isoCA-4, clearlyi ndicating that it is possible to replace the 3,4,5-trimethoxyphenyl Aring of isoCA-4 by aq uinazoline ring with no significant loss of biological activity.…”
Section: In Vitro Cell Growth Assaysmentioning
confidence: 85%
See 2 more Smart Citations
“…Seven compounds-4a, 4b, 4c, 4d, 4i, 4k,a nd 4l-were found to have strong growth inhibitory activity against HCT116 cells, with GI 50 values lower than 50 nm.A sw ep reviously observed with other isoCA-4 analogues, [17,21,34,35] compounds 4b,4c ,a nd 4d,w hich respectively bear the greatest resemblancet oisoCA-4, isoFCA-4, and iso-NH 2 CA-4, possessed the highest potency,i nhibiting the growth of HCT116 cells with GI 50 values ranging from 10 to 18 nm. These GI 50 values are similart ot hose obtained with isoCA-4, clearlyi ndicating that it is possible to replace the 3,4,5-trimethoxyphenyl Aring of isoCA-4 by aq uinazoline ring with no significant loss of biological activity.…”
Section: In Vitro Cell Growth Assaysmentioning
confidence: 85%
“…[12][13][14][15] Our strategy in the field of CA-4 research is focusedo nr eplacement of the unstable Z-double bond with severall inkers [16,17] of various sizes, from which the one-atom linker was found to produce the optimal length between the two aromaticr ings Aa nd B. These studies revealed novel promising classes of non-isomerizable CA-4 analogues, [17] including 1,1-diarylethylenes 1, [18,19] 1,1-diarylethanes 2, [20] and azaisoerianin derivatives 3 [21] (Figure 1). Thus, we have demonstrated that it is possible to replacet he Z-1,2-diarylethylene scaffold of CA-4 with 1,1-diarylethylene to give isoCA-4, as tructural isomer of CA-4, with biological activities similar to those of the natural product.…”
Section: Introduction Combretastatinmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic method is simple without the control of cis-configuration [30,31]. The Alami group have completed plentiful studies on the modification of 1,1-diaryl double bond scaffold using naphthenic [32], naphthalene [33], arylchromenes [34], azaisoerianin [35], arylbenzoxepins [36], etc. In our previous works [37], dihydrofuran and dihydroisoxazole analogues of isoCA-4 were prepared through [3+2] reactions and could inhibit tubulin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Moreover, this easy to synthesize and stable 1,1-diarylethylene derivative [13,14,15] disrupted newly formed vascular tubes in vitro after only 3 h of treatment when it was added at a concentration of 10 nM, to human umbilical vein endothelial cells (HUVECs) thus demonstrating an anti-vascular effect associated to an improved in vivo efficacy. [16] In view of the establishment of structure-activity relationships (SARs) we have reported that it was allowed to reduce the ethylene double bond (isoerianin derivatives) [17] and to replace the 1,1-ethylene double bond of such drugs by a N-Me function (isoazaerianin derivatives) [18] with no loss of anti-cancer efficiency. Later, by structural modifications on the A-ring of isoCA-4, we have synthesized a series of highly potent cytotoxic isocombretaquinazolines (isoCoQs) [19] and isocombretaQuinolines (isoCoQuines) [20] demonstrating for the first time, that the 3,4,5-trimethoxyphenyl A-ring present in CA-4 and isoCA-4 can be replaced in these structures by various nitrogen-containing heterocyclic systems.…”
Section: Introductionmentioning
confidence: 99%